All-Dielectric Dual-Band Anisotropic Zero-Index Materials - Baoyin Sun; Ran Mei; Mingyan Li; Yadong Xu; Jie Luo; Youwen Liu (Photonics)
Zero-index materials, characterized by near-zero permittivity and/or permeability, represent a distinctive class of materials that exhibit a range of novel physical phenomena and have potential for various advanced applications. However, conventional zero-index materials are often hindered by constraints such as narrow bandwidth and significant material loss at high frequencies. Here, we numerically demonstrate a scheme for realizing low-loss all-dielectric dual-band anisotropic zero-index materials utilizing three-dimensional terahertz silicon photonic crystals. The designed silicon photonic crystal supports dual semi-Dirac cones with linear-parabolic dispersions at two distinct frequencies, functioning as an effective double-zero material along two specific propagation directions and as an impedance-mismatched single-zero material along the orthogonal direction at the two frequencies. Highly anisotropic wave transport properties arising from the unique dispersion and extreme anisotropy are further demonstrated. Our findings not only show a novel methodology for achieving low-loss zero-index materials with expanded operational frequencies but also open up promising avenues for advanced electromagnetic wave manipulation.